Analysis of Stuck Pipe Incidents in Khabaz Field - Said Amina, Nazaneen; A.Alhaleemb, Ayad (Iraqi Journal of Chemical and Petroleum Engineering, 2018)
There are many events which causes nonproductive time (NPT) in the drilling industry. The mostly effective in this NPT is pipe sticking event. A considerable amount of time and resources can be spent in efforts to free a stuck pipe. In addition, Unsuccessful fishing operations results in costly alternatives including side-tracking. The drilling in Khabaz oil field poses many operational challenges among of them stuck pipe , lost circulation, flow of salt water during drilling, and hole caving. Stuck pipe can be considered the quite difficult problem in Khabaz oil field due to associated incidents which lead to NPT activities. Well Khabaz -34 was selected to study the problem of stuck pipe in this field. An analysis of stuck pipe events was made by using the graphical analysis software Easy View. The results were then discussed to identify the causes of stuck pipe. Finally, recommendation to select proper type /drilling fluid rheology properties, optimize casing seat design to reduce probability of stuck pipe.